First record of the family Prodoxidae (Lepidoptera: Adeloidea), Lampronia flavimitrella (Hübner), reported from Korea - Minyoung Kim; Young-Mi Park (Journal of Asia-Pacific Biodiversity, 2016)
The family Prodoxidae is recorded for the first time from Korea, reporting Lampronia flavimitrella (Hübner) which was collected at Jeju-do Island. Redescription of the adult is given, with images of adult and male genitalia.